L-Glutamine is better for treatment than prevention in exhaustive exercise - Lu, Cheng-Chung; Ke, Chun-Yen; Wu, Wen-Tien; Lee, Ru-Ping (Frontiers in Physiology, 2023)
Introduction: Glutamine is known as the richest nonessential amino acid in the human body. The intake of glutamine is not only beneficial to nutrition but also reported to enhance inflammation reducing bioactivity in exercise. Although studies have demonstrated that glutamine is beneficial for exercise, the optimal intake timing remains unclear. This study examined whether the effects of glutamine on tissue damage and physiology differ between intake timings. Methods: Rats were divided into without L-glutamine supplementation (vehicle), with L-glutamine before exhaustive exercise (prevention), and with L-glutamine after exhaustive exercise (treatment) groups. Exhaustive exercise was induced by treadmill running and L-glutamine was given by oral feeding. The exhaustive exercise began at a speed of 10 miles/min and increased in increments of 1 mile/min, to a maximum running speed of 15 miles/min with no incline. The blood samples were collected before exhaustive exercise, 12 h and 24 h after exercise to compare the creatine kinase isozyme MM (CK-MM), red blood cell count and platelet count. The animals were euthanized on 24 h after exercise, and tissue samples were collected for pathological examination and scored the severity of organ injury from 0 to 4. Results: The CK-MM was elevated gradually after exercise in the vehicle group; however, CK-MM was decreased after L-glutamine supplementation in the treatment group. The treatment group had higher red blood cell count and platelet count than the vehicle and prevention group after exercise. In addition, the treatment group had less tissue injury in the cardiac muscles, and kidneys than prevention group. Conclusion: The therapeutic effect of L-glutamine after exhaustive exercise was more effective than preventive before exercise.